Areas of plant diversity—What do we know?. Issue 1 (21st May 2020) - Brummitt, Neil; Araújo, Ana Claudia; Harris, Timothy
Societal Impact Statement: Identifying regions of the world that are rich in plant species will enable conservation efforts to be more effectively targeted. We present a review of global studies of plant diversity, including novel analyses from our own work, and highlight areas of the world that are consistently identified by multiple studies utilizing varied data sets as being particularly rich in plant species. This will be of interest to botanical professionals and conservationists seeking to identify and conserve priority species‐rich environments, including those working to progress international conservation targets, and to all those interested in the global distribution of biodiversity and its conservation. Summary: Areas of high diversity for vascular plants, both for numbers of species and of endemic species, are by now well established and in agreement across a variety of studies using a wide range of data from different sources. Here we review the current state of knowledge of geographical patterns of plant diversity around the world, compare this with our knowledge of vertebrate taxonomic groups, and reflect on next steps for better characterizing patterns of diversity in order to achieve effective conservation prioritization. We illustrate this with analyses of geographical patterns of plant diversity from three different data types with differing degrees of geographical and ecological resolution. At broad spatial scales these analyses are largely congruent with each other and with areas of high diversity and endemism for species of terrestrial vertebrates. Abstract : Identifying regions of the world that are rich in plant species will enable conservation efforts to be more effectively targeted. We present a review of global studies of plant diversity, including novel analyses from our own work, and highlight areas of the world that are consistently identified by multiple studies utilizing varied data sets as being particularly rich in plant species. This will be of interest to botanical professionals and conservationists seeking to identify and conserve priority species‐rich environments, including those working to progress international conservation targets, and to all those interested in the global distribution of biodiversity and its conservation.